VALIDITY OF BITARAKSA (SPACE ORBIT) AS A LEARNING MEDIA IN CLASS VII SOLAR SYSTEM MATERIAL - Dyah Ismi Safitri; Noer Af’idah (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2024)
Learning media is a tool that can convey information from teachers to students. This is because the use of learning media can make learning activities more efficient. However, so far teachers still rarely use learning media. This causes learning activities to seem boring and students often experience difficulties in understanding the material. The solar system matari in science lessons is one of the materials that requires learning media. The purpose of this study is to determine the validity of the development of bitaraksa media in learning solar system science for grade VII junior high school students. This study uses the ADDIE development method, which consists of five stages, namely the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage, but in this study the implementation stage is not carried out. The validity test was carried out by media assessment by media expert Validators, material experts and junior high school science teachers. From filling out the validation sheet, results were obtained in the form of qualitative and quantitative data. The quantitative data obtained was processed to obtain the validity value of the developed bitaraksa media. Meanwhile, qualitative data in the form of suggestions and inputs are used as a reference to improve and revise bitaraksa media developed by researchers. Based on the results of quantitative data, the average score of 87.1% of the bitaraksa media validation assessment was obtained, the category was very valid.